Return-to-Work Policies' Clawback Regime and Labor Supply in Disability Insurance Programs - Arezou Zaresani; Miguel Olivo-Villabrille (Institute of Labor Economics (IZA), 2021)
Exploiting a quasi-natural experiment and using administrative data, we examine the effects of the return-to-work policies' clawback regime in Disability Insurance (DI) programs on beneficiaries' labor supply decisions, allowing them to collect reduced DI payments while working. We compare two return-to-work policies: one with a single rate clawback regime and another with a progressive clawback regime where a reform further increased its progressiveness. The reform caused an increase in the mean labor supply; beneficiaries who already work, work more, and those who did not work start working. The effects are heterogeneous by beneficiaries characteristics, and the increase is driven mainly by top percentiles of earnings. Findings suggest an essential role for the clawback regime in return-to-work policies and targeted policies to increase the labor supply in DI programs.
Keywords: D3; H3; I3; J3; 330; disability insurance; clawback rate; return-to-work policy; financial incentives; labor supply